A Novel Osteogenic Cell Line That Differentiates Into GFP‐Tagged Osteocytes and Forms Mineral With a Bone‐Like Lacunocanalicular Structure. (7th June 2019) - Wang, Kun; Le, Lisa; Chun, Brad M; Tiede‐Lewis, LeAnn M; Shiflett, Lora A; Prideaux, Matthew; Campos, Richard S; Veno, Patricia A; Xie, Yixia; Dusevich, Vladimir; Bonewald, Lynda F; Dallas, Sarah L
ABSTRACT: Osteocytes, the most abundant cells in bone, were once thought to be inactive, but are now known to have multifunctional roles in bone, including in mechanotransduction, regulation of osteoblast and osteoclast function and phosphate homeostasis. Because osteocytes are embedded in a mineralized matrix and are challenging to study, there is a need for new tools and cell models to understand their biology. We have generated two clonal osteogenic cell lines, OmGFP66 and OmGFP10, by immortalization of primary bone cells from mice expressing a membrane‐targeted GFP driven by the Dmp1 ‐promoter. One of these clones, OmGFP66, has unique properties compared with previous osteogenic and osteocyte cell models and forms 3‐dimensional mineralized bone‐like structures, containing highly dendritic GFP‐positive osteocytes, embedded in clearly defined lacunae. Confocal and electron microscopy showed that structurally and morphologically, these bone‐like structures resemble bone in vivo, even mimicking the lacunocanalicular ultrastructure and 3D spacing of in vivo osteocytes. In osteogenic conditions, OmGFP66 cells express alkaline phosphatase (ALP), produce a mineralized type I collagen matrix, and constitutively express the early osteocyte marker, E11/gp38. With differentiation they express osteocyte markers, Dmp1, Phex, Mepe, Fgf23, and the mature osteocyte marker, Sost. They also express RankL, Opg, and Hif1α, and show expected osteocyte responses to PTH, including downregulation of Sost, Dmp1, and Opg and upregulation of RankL and E11/gp38 . Live cell imaging revealed the dynamic process by which OmGFP66 bone‐like structures form, the motile properties of embedding osteocytes and the integration of osteocyte differentiation with mineralization. The OmGFP10 clone showed an osteocyte gene expression profile similar to OmGFP66, but formed less organized bone nodule‐like mineral, similar to other osteogenic cell models. Not only do these cell lines provide useful new tools for mechanistic and dynamic studies of osteocyte differentiation, function, and biomineralization, but OmGFP66 cells have the unique property of modeling osteocytes in their natural bone microenvironment. © 2019 American Society for Bone and Mineral Research